2010
DOI: 10.1007/s00421-010-1369-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wind and rain on thermal responses of humans in a mildly cold environment

Abstract: The purpose of the present study was to clarify the effects of wind and rain on peripheral heat loss by non-exercising minimally clothed humans in a mildly cold environment. Seven healthy young male subjects wearing only shorts rested in a standing position for 20 min at an ambient temperature of 15 degrees C under three conditions: without exposure to wind or rain (CON), with exposure to wind (3 m/s) (WIND) and with exposure to wind (3 m/s) and rain (40 mm/h) (WIND + RAIN). Mean heat loss measured using a hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…We found that rainfall had a negative effect on activity and that the negative effect was more pronounced when the temperature was low. Yamane et al [ 57 ] showed that, at an ambient temperature of 15°C, lightly clothed humans lost twice as much heat in conditions with rainfall than in conditions without rainfall, and heat production increased 2.5 times. Therefore, getting wet may impose a serious thermoregulatory problem for macaques.…”
Section: Discussionmentioning
confidence: 99%
“…We found that rainfall had a negative effect on activity and that the negative effect was more pronounced when the temperature was low. Yamane et al [ 57 ] showed that, at an ambient temperature of 15°C, lightly clothed humans lost twice as much heat in conditions with rainfall than in conditions without rainfall, and heat production increased 2.5 times. Therefore, getting wet may impose a serious thermoregulatory problem for macaques.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of perceived exertion (RPE) was determined using the Borg scale immediately after each exercise period [ 3 ] . In the cold condition experiment, subjects were asked about the presence of shivering every 2 min during the rest periods, and the time of shivering onset was recorded [ 31 ] .…”
Section: Rate Of Perceived Exertion and Shiveringmentioning
confidence: 99%
“…Adding moisture, even humidity, to the equation results in significantly greater body temperature loss due to conduction and evaporative cooling (Parsons, 2014). Exposure to wet and cold environments result in dramatically higher metabolic stress and thermal loss than in dry conditions (Thompson and Hayward, 1996; Weller et al, 1997; Yamane et al, 2010). Thompson and Hayward (1996) reported a 10°C reduction in rectal temperature in healthy men after just 2 h of exposure to wet and cold conditions.…”
mentioning
confidence: 99%